Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik - Ratna Apriyatiningsih (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
To develop student learning outcomes in chemistry learning, teachers must be able to choose appropriate learning models to be applied in the learning process with a scientific approach. The aim of this research is to improve student learning outcomes through the application of Project Based Learning. The research was conducted qualitatively using descriptive methods on 20 students in class XI Science at SMAN 1 Bojonegara studying chemistry. Based on the research results, it is known that the results of assessing students’ knowledge increased from the beginning of learning by 35% to 90% achieving the Minimum Completeness Criteria.